Short- and Long- Run Relationships among Remittance, GDP, Inflation and Interest Rates in Nepal (Prithvi Academic Journal, 2026)
This study examined the long- and short-term relationships between remittance, Gross Domestic Product (GDP), inflation and interest rates in Nepal. This study used time-series data from 2003 to 2024 from the world bank and Nepal Rastra Bank (NRB). The study applied econometric techniques including the Phillips-Perron unit root test, Johansen cointegration test, and Vector Error Correction Model (VECM) to analyse the dynamics among the variables. The Johansen cointegration test indicated three long-run cointegration relationships among the variables. The VECM shows that the GDP, inflation and interest rates in the long run adjust significantly to restore equilibrium when deviations occur. This might suggest a contractionary process of the economy where policies aimed at controlling inflation or excess money supply might restrain the GDP. Meanwhile, remittances tend to increase in response to economic downturns, acting as a buffer for the economy. Short-run analysis showed that past values of GDP, inflation and interest rates strongly influence their current behaviour. This might suggest structural rigidity or gradual policy transmission. Meanwhile, remittance inflow reacts positively to interest rate and negatively to inflation. This means maintaining a stable interest rate and low inflation can ensure sustained remittance flow. The study concludes that maintaining stable interest rates and low inflation ensures sustainable remittance inflows and overall macroeconomic stability in Nepal. It is recommended that policymakers channel remittance into productive sectors to enhance economic growth while minimising inflationary pressures.